Queering Agatha Christie Revisiting the Golden Age of Detective Fiction - Bernthal, J.C.; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This book is the first fully theorized queer reading of a Golden Age British crime writer. Agatha Christie was the most commercially successful novelist of the twentieth century, and her fiction remains popular. She created such memorable characters as Hercule Poirot and Jane Marple, and has become synonymous with a nostalgic, conservative tradition of crime fiction. J.C. Bernthal reads Christie through the lens of queer theory, uncovering a playful, alert, and subversive social commentary. After considering Christie's emergence in a commercial market hostile to her sex, in Queering Agatha Christie Bernthal explores homophobic stereotypes, gender performativity, queer children, and masquerade in key texts published between 1920 and 1952. Christie engaged with debates around human identity in a unique historical period affected by two world wars. The final chapter considers twenty-first century Poirot and Marple adaptations, with visible LGBT characters, and poses the question: might the books be queerer?
Introduction -- Chapter 1. Constructing Agatha Christie -- Chapter 2. English Masculinity and its Others -- Chapter 3. Femininity and Masquerade -- Chapter 4. Queer Children, Crooked Houses -- Chapter 5. Queering Christie on Television -- Conclusion.
Keywords: Literature, Modern-20th century; Fiction; British literature